2022
DOI: 10.3389/fnagi.2022.899944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomes as Mediators of Neuroinflammation in the Pathogenesis and Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease characterized by progressive dementia. Accumulation of β–amyloid peptide 1–42 and phosphorylation of tau protein in the brain are the two main pathological features of AD. However, comprehensive studies have shown that neuroinflammation also plays a crucial role in the pathogenesis of AD. Neuroinflammation is associated with neuronal death and abnormal protein aggregation and promotes the pathological process of β-amyloid peptide 1–42 and tau prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 119 publications
0
13
0
Order By: Relevance
“…In the 9 month 5XFAD colon tissue dataset, vesicle-mediated transport ( p = 8.53*10 −13 ) and lipid metabolic processes ( p = 9.82*10 −12 ) were the top two enriched pathways ( Figure 2 D). Immune responses, vesicle transportation, and lipid metabolism mutually affect each other in AD [ 39 , 40 , 41 ]. This cross-sectional proteomic analysis suggested that 5XFAD mouse colonic tissue underwent time-sensitive and complex proteomic alterations during AD development, with striking shifts away from early immune response signatures at 3 and 6 months to dysregulated lipid metabolism at 9 months ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…In the 9 month 5XFAD colon tissue dataset, vesicle-mediated transport ( p = 8.53*10 −13 ) and lipid metabolic processes ( p = 9.82*10 −12 ) were the top two enriched pathways ( Figure 2 D). Immune responses, vesicle transportation, and lipid metabolism mutually affect each other in AD [ 39 , 40 , 41 ]. This cross-sectional proteomic analysis suggested that 5XFAD mouse colonic tissue underwent time-sensitive and complex proteomic alterations during AD development, with striking shifts away from early immune response signatures at 3 and 6 months to dysregulated lipid metabolism at 9 months ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…And revealing the regulatory mechanism of ncRNAs in AD from the perspective of neuroinflammation can provide new ideas for the treatment of AD ( Lan et al, 2021 ; Zingale et al, 2021 ). A recent review article also shows that ncRNAs in exosomes can mediate nerve inflammation and promote the development of AD ( Weng et al, 2022 ). In addition, memory deficits are the main characteristics of AD, and improving memory deficits by regulating ncRNAs is also a future research direction ( Ju et al, 2021 ; Xiao et al, 2021 ; Zhang G. J. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various types of inflammasomes are also present in the cytosol of microglia, astrocytes, and neurons, where their activation contributes to the development and progression of neurodegenerative diseases in which inflammation is considered a common pathophysiological mechanism [ 1 , 247 , 248 ]. Neuroinflammation may involve exosomes that transport Aβ, tau, inflammatory factors, and other pathogenic substances between microglia, astrocytes, and neurons [ 249 , 250 ]. Exosome-inflammasome crosstalk has been documented: inflammasome activation can regulate exosomes release, and exosomes are an upstream regulator for inflammasome activation or inhibition [ 251 ].…”
Section: Hypotheses Of Alzheimer’s Diseasementioning
confidence: 99%